Єврорегіони: характеристика та принципи функціонування - Куцин, А. Р.; Передало, Х. С. (Видавництво Львівської політехніки, 2016)
Розглянуто тлумачення поняття “транскордонне співробітництво” та єврорегіонів у міжнародному праві та українським законодавством, проаналізована діяльність єврорегіонів, що функціонують в Україні на цьому етапі розвитку транскордонного співробітництва. Сформульовано принципи здійснення транскордонного співробітництва. The article investigates the theoretical aspects of cross-border cooperation. The aim of the article is to create principles of cross-border cooperation and to consider euroregions and it’s features. The analysis of the term definitions showed that cross-border cooperation is joint actions aimed on deepening and strengthening good neighbor relations between territorial communities or authorities within the jurisdiction. The article specifies the characteristic features of such euroregions as: “Carpathian euroregion”, “Bug”, “Lower Danube”, “Upper Prut”, “Dnipro”, “Slobozhanschyna” and “Dnister”. It is shown that common purpose and activities of these euroregions is organization and coordination of measures to promote cooperation in the fields of economy, science, culture, health, education and sports. After analyzing the patterns of the existence and development of euroregions and crossborder cooperation in general, we can see that it’s implemented in the following stages: 1. Investigation of existing links between partners; 2.Choosing and implementation of development strategy; 3.Creating and providing development programs; 4.Analysis and evaluation. According to these stages principles of cross-border cooperation are identified. They are the principle of partnership, the principle of attraction, the principle of participation, the principle of didacticism, the principle of informativeness, the principle of objectivity. As it’s shown in article Ukraine has some achievements in the development of crossborder cooperation. This positive side is that Ukraine started program of training staff for cross-border cooperation, formed the basis of the legal framework of cross-border cooperation, which always requires changes to the relevant international law, the development and implementation of new laws. Also country realised and improved state regional policy on crossborder cooperation, created seven euroregions, organised cooperation with border areas. The problem is that there is no single, unified organisational and financial platform of implementation of regional policy on cross-border cooperation.
Cross-border cooperation: general characteristics and principles of formation
Keywords: координація; прикордонні території; єврорегіон; транскордонне співробітництв; coordination; border areas; euroregion; cross-border cooperation